ExoMars Atmospheric Mars Entry and Landing Investigations and Analysis (AMELIA) - Ferri, F.; Karatekin, Ö.; Lewis, S.; Forget, F.; Aboudan, A.; Colombatti, G.; Bettanini, C.; Debei, S.; Van Hove, B.; Dehant, V.; Harri, A.; Leese, M.; et al. (2019)
The entry, descent and landing of Schiaparelli, the ExoMars Entry, descent and landing Demonstrator Module (EDM), offered a rare (once-per-mission) opportunity for in situ investigations of the martian environment over a wide altitude range. The aim of the ExoMars AMELIA experiment was to exploit the Entry, Descent and Landing System (EDLS) engineering measurements for scientific investigations of Mars’ atmosphere and surface. Here we present the simulations, modelling and the planned investigations prior to the Entry, Descent and Landing (EDL) event that took place on 19th October 2016. Despite the unfortunate conclusion of the Schiaparelli mission, flight data recorded during the entry and the descent until the loss of signal, have been recovered. These flight data, although limited and affected by transmission interruptions and malfunctions, are essential for investigating the anomaly and validating the EDL operation, but can also contribute towards the partial achievement of AMELIA science objectives.